ANALISIS PERSEPSI DAN PREFERENSI MASYARAKAT TERHADAP REPUTASI PEMERINGKAT PERGURUAN TINGGI - Gunarto, Muji; Gaffar, Vanessa (Universitas muhammadiyah palembang, 2016)
Consumers will consider various attributes or factors when they make a purchase or deciding on a college choice. The Minister of Research, Technology and Higher Education of the Republic of Indonesia has classified and rank national universities. Previously, some agencies have classified and rank universities both nationally and globally. The results of classification or ranking are different from each other because they use different methods and different sizes.The purpose of this study is to analyze public perception of the reputation of the institution that has to rank colleges and community preferences on college choice. Method survey conducted on three groups of people, they consists of some students, lecturers and the general public.The sampling technique used isaccidental sampling. The number of respondents in this research is 123 respondents. The analysis technique used is descriptive analysis and conjoint analysis. The results show that many people do not recognize the results of the classification and ranking universities from an independent agencies, the majority of respondents only recognize BAN-PT as an institution that performs the classification of colleges. However, the results of ranking colleges taken seriously by the leaders and managers of higher education as a basic policy to achieve the best college. In addition, the public preference towards higher education shows a high score with various aspects of consideration, and universities should be able to give a good experience to their students.Almost all aspects of preferences offered highly rated, except for the aspect of prestige. The highest preference in choosing a college is a reputable college and study program that conformity with their interests.